2014
DOI: 10.4236/jct.2014.55047
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Sex and Non-Sex Hormones and Distribution Features of Blood ABO System Groups among the Women with Uterine Body Tumors

Abstract: Objectives: The aim of the investigation was to study the hormonal status (sex hormones: estradiol (E 2), progesterone (P), testosterone (T); non-sex gonadotropic hormones-luteinizing hormone (LH) and follicle-stimulating hormone (FSH)) of women with benign and malignant tumors of uterine body in the reproductive, menopause and postmenopause periods. Also the distribution features of the blood ABO system phenotype groups and their link to the development of uterine body tumors have been studied. Methods: The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…On contrary, the O blood group was associated with high risk of EC in menopause and post-menopause women 21 and in another study no statistically significant correlations were obtained for EC and ABO 22 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…On contrary, the O blood group was associated with high risk of EC in menopause and post-menopause women 21 and in another study no statistically significant correlations were obtained for EC and ABO 22 .…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies reported that the A blood group was associated with high risk of EC 29 particularly in reproductive age 21 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Соответственно, повышается и/или снижается риск развития различных заболеваний щитовидной железы, в том числе аутоиммунных; кроме того, функция щитовидной железы может участвовать в патогенезе других климактерических осложнений [33]. Они также изменяют синтез половых стероидных гормонов [34], что значительно повышает риск развития заболеваний женских репродуктивных органов, в том числе опухолей [35,36].…”
Section: Discussionunclassified
“…Встановлено підвищений ризик розвитку раку молочної залози, товстої кишки, підшлунковаї залози, стравоходу, сечового міхура, яєчників, легень, шкіри, щитовидної залози, печінки з груповими еритроцитарними антигенами. Також доведено вплив антигенів груп крові АВ0, Rhesus, Kell на ступінь диференціювання злоякісних клітин, а також чутливість пухлини до терапії, загальну виживаність (Yuzhalin and Kutikhin, 2012;Pelzer et al, 2013;Urun et al, 2013;Abobaker et al, 2014;Aly et al, 2014;Cao et al, 2014;Kumar et al, 2014;Mansour et al, 2014;Nakashidze et al, 2014;Upma and Fotra, 2016). Іноді дані про розподіл антигенів еритроцитів у хворих із різною патологією неоднозначні, але наявність тих або інших еритроцитарних специфічностей у людини може бути фактором ризику виникнення певного захворювання, у тому числі й онкогематологічного (Cihan, 2014;Mansour et al, 2014;Engel et al, 2015;Flegr, 2016).…”
Section: вступunclassified